Carcharhinus obscurus - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
□ Carcharhinus obscurus (Lesueur, 1818) – Dusky shark; Tubarão-faqueta ① , ② , Faqueta ③ According to Ebert & Stehmann (2013) the records of this species from the Azores might concern C. galapagensis . Details are given above for the species C. galapagensis . : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 12, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515 : {"references": ["Ebert D. A. & Stehmann M. F. W. 2013. Sharks, batoids, and chimaeras of the North Atlantic. FAO Species Catalogue for Fishery Purposes no. 7, Food and Agriculture Organization, Rome."]}